4th IEEE International Conference on Digital Ecosystems and Technologies 2010
DOI: 10.1109/dest.2010.5610654
|View full text |Cite
|
Sign up to set email alerts
|

A real case study of assistive living ecosystems

Abstract: Assistive technologies are directly linked to the elderly and the disabled people. The necessary services offered by an assistive technologies ecosystem are provided mostly through internet. It is also well known that elderly and disabled people find difficult to access the internet. The resulting challenge is to discover a combination of assistive technologies, meaning devices and software interface characteristics in order to give the opportunity to elderly and disabled to access the internet and enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The literature review revealed that this sub-group was highly relevant, with 129 unique publications discussing ICT in the context of disability. Within these publications, the core focus was on designing technologies for better web (Sevilla et al, 2007;Cooper et al, 2012) and environmental (within the user's physical location) (Wills et al, 2010) accessibility and usability (Jhangiani, 2006;Wentz and Lazar, 2011).…”
Section: Technological Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review revealed that this sub-group was highly relevant, with 129 unique publications discussing ICT in the context of disability. Within these publications, the core focus was on designing technologies for better web (Sevilla et al, 2007;Cooper et al, 2012) and environmental (within the user's physical location) (Wills et al, 2010) accessibility and usability (Jhangiani, 2006;Wentz and Lazar, 2011).…”
Section: Technological Dimensionmentioning
confidence: 99%
“…Similarly, Carr et al (2001) noted that assistive technology allows people to continue in their normal roles and meet their expectations of life despite their physical impairments or disabilities. The literature review revealed 54 publications that actively discussed the importance and use of assistive technology, with various case studies discussing assistive ecosystems, such as creating and selling software made for people with impairments (Wills et al, 2010;Verstockt et al, 2009;Iacopetti et al, 2008) and communication platforms for the physically impaired (Guerreiro et al, 2009;Keskinen et al, 2012).…”
Section: Technological Dimensionmentioning
confidence: 99%